Morphological development, in vitro storage, and regeneration of protocorm-like bodies of orchid hybrid Dendrobium Shavin White - Bustam, Suryanti (2013)
This study was carried out to establish a method for storage of orchid protocorm-like bodies (PLBs) in order to improve the handling and transport of the propagules. Identifying the developmental stages of PLBs is an important criteria in ensuring increased plantlet regeneration potential while the ability to store PLBs allows the accumulation of large number of PLBs which can facilitate the production of uniform plants for commercial planting. Initially, observation on growth and development of PLBs were made using stereomicroscope and variable pressure scanning electron microscopy (VPSEM) to identify the time taken for growth and development to occur. The study revealed that secondary PLBs were formed from single isolated PLBs after 4 – 7 weeks of culture upon the initiation of embryos after 2 - 3 weeks of culture. Shoots were found to be initiated from newly formed PLBs after 5 – 7 weeks of culture. This was followed by selection of the best PLBs developmental stage as at one time PLBs varying in size and maturity stage can be obtained. The PLBs were categorized into five based on size and presence or absence of shoot namely ≤ 2 mm (S1), >2 – 4 mm (S2), >4 – 6 mm (S3), >2 – 4 mm with shoot (S4) and >4 – 6 mm with shoot (S5). Results from this experiment showed that PLBs with shoot (S4 and S5) gave significantly higher conversion percentage (85% and 90% respectively) as compared to the PLBs without shoot (S1, S2 and S3) when cultured on semi-solid ½ MS basal medium devoid of plant growth regulators irrespective of size. In the second part of the study naked or encapsulated PLBs were kept in air tight container stored in darkness at different temperatures namely 5°C, 10°C, 25°C ± 2 and 30°C ± 2. Naked PLBs can be efficiently stored at 25°C ± 2 where high viability percentages (88 – 100%) were obtained even after 135 days of storage. Meanwhile encapsulated PLBs also showed the best response when stored at 25°C ± 2. At 25°C ± 2, encapsulated PLBs stored for 75 days retained 80 – 92% conversion while 52% was obtained after 135 days of storage. Subsequently, the feasibility of germinating synthetic seeds of Dendrobium Shavin White in different substrates was tested. The different substrates include M1 (semi-solid ½ MS basal medium), M2 (cotton irrigated with sterilized liquid ½ MS basal medium),M3 (cotton irrigated with sterilized distilled water) and M4 (cotton irrigated with nonsterilized distilled water). The encapsulated PLBs regenerated well in M1 where 96% of encapsulated PLBs germinated and 76% of them converted into plantlets. Results from this study revealed that although optimum results were recorded by inoculating encapsulated PLBs in M1, they can also be regenerated using M2 or M3 with 72% and 56% germination and 64% and 44% conversion respectively. The present study established that selection of PLBs is important as it ensures rapid conversion into plantlet. PLBs varying in size ranging for 2 – 6 mm can be used provided the shoot initials are present. Suitable PLBs can be effectively stored at 25°C ±2 for 135 days in the naked form in air tight container, retaining 80 – 92% of PLBs converted into plantlet or in the encapsulated form with 52%. In addition this study showed that encapsulated PLBs can technically function as normal seeds in relation to germination whereby encapsulated PLBs can germinate with the supply of sterilized distilled water.